MULTI GEOPHYSICAL OBSERVATIONS AT BLAWAN - IJEN VOLCANO GEOTHERMAL COMPLEX FOR REGIONAL DEVELOPMENT - Sukir Maryanto; Agus S Wicaksono; Anjar P Azhari; Cinantya N Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2015)
Geothermal resource investigation by using multi geophysical observation was accomplished for Blawan-Ijen geothermal system. Geological and surface investigation found about 21 hot springs have been found in Blawan area with the surface temperature ranged from about 40oC-55oC. Based on resistivity and GPR data known that the underground seepage of hot water following the fault direction. This fault structure is identified based on the high distribution of microseismicity and thermal infrared remote sensing (TIR) analysis which associated with high land surface temperature (LST). Meanwhile, the heat source of Blawan - Ijen geothermal system are found in the southwest part based on high magnetic anomaly which represents the igneous rocks. All methods used shows the results indicating that Blawan-Ijen volcano complex is an interesting area for geothermal energy development and suitable for pilot project on regional development of volcano geothermal region.